2018
DOI: 10.1097/hmr.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HCAHPS scores from hospitals’ social media pages: A sentiment analysis

Abstract: Administrators can tap into the wealth of commentary on social media as the forum continues to expand its influence in health care. Comments on social media may also serve as an early snapshot of patient-reported experiences, alerting administrators to problems that may appear in subsequent HCAHPS survey results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…Reviews of practices on social media may be helpful in obtaining feedback about patient care and visits. 7 This could be applied to further improve the patient experience and optimize the flow and efficiency of ophthalmic practices.…”
Section: Use Of Social Media In Clinical Practicementioning
confidence: 99%
“…Reviews of practices on social media may be helpful in obtaining feedback about patient care and visits. 7 This could be applied to further improve the patient experience and optimize the flow and efficiency of ophthalmic practices.…”
Section: Use Of Social Media In Clinical Practicementioning
confidence: 99%
“…To the Editor: The choice of epidermal suture is largely a stylistic choice by surgeons, as numerous studies have found equivalent outcomes from nonabsorbable sutures removed after 5 days, long-acting absorbable sutures removed after 5 days, 1,2 and rapidly absorbable sutures that are not removed. 3 Fast-absorbing gut sutures are often used in dermatologic surgery on the face but are commonly coated with petrolatum 4 to improve tissue-handling characteristics.…”
Section: Effect Of Petrolatum Coating On Fast-absorbing Gut Suturementioning
confidence: 99%
“…To the Editor: Apremilast monotherapy has generated considerable excitement as an oral option for the treatment of psoriasis because of its favorable efficacy and safety profile based on its pivotal randomized controlled trials, ESTEEM 1 and 2. 1,2 In real-world practice, it is sometimes used in combination with biologic agents and conventional systemic agents to control residual psoriasis that cannot be managed with 1 agent alone. Our research group previously published our findings comparing the efficacy and safety of apremilast monotherapy with combination therapy during an initial 16-week treatment phase in real-world…”
Section: Effect Of Petrolatum Coating On Fast-absorbing Gut Suturementioning
confidence: 99%
“…The internet offers a large number of websites where healthcare services might be rated, ranging from commercial sites like Yelp.com to public sites like NHS Choices. Research on web rating sites has grown rapidly in recent years, covering topics such as the content of comments on rating sites,1–3 efforts to produce quantitative scores from qualitative comments,4 and correlation studies between ratings on websites and established quality indicators such as patient experiences, mortality and readmission 5–9. Previous research shows that rating sites include comments on similar topics to research-based patient experience questionnaires but also that various additional topics are described 1–3.…”
Section: Introductionmentioning
confidence: 99%
“…Facebook ratings have been included in several previous studies, mostly for hospital services4 10–14 but also for nursing homes 15. As for other web rating sites, Facebook studies in the hospital setting have shown low to moderate association between Facebook ratings and indicators from systematic patient experience surveys.…”
Section: Introductionmentioning
confidence: 99%